Developing instruments to assess and compare the quality of engineering education: the case of China and Russia. Issue 5 (3rd July 2016) - Kardanova, Elena; Loyalka, Prashant; Chirikov, Igor; Liu, Lydia; Li, Guirong; Wang, Huan; Enchikova, Ekaterina; Shi, Henry; Johnson, Natalie
Abstract : Relatively little is known about differences in the quality of engineering education within and across countries because of the lack of valid instruments that allow for the assessment and comparison of engineering students' skill gains. The purpose of our study is to develop and validate instruments that can be used to compare student skill gains in mathematics and physics courses in undergraduate engineering programmes across countries. The approach includes procedures to establish construct validity and other necessary psychometric properties. Drawing on data collected from over 24 engineering experts and 3600 engineering students across Russia and China, we establish that it is possible to develop valid, equitable and cross-nationally comparable instruments that can assess and compare skill gains.